Construction of a cDNA clone corresponding to mouse alpha 1(IV) procollagen. - dos Santos, C L (1984)
A new procedure for the synthesis of double stranded cDNA, based upon release of mRNA by "in vitro" translation, was used to clone type IV collagen. Collagen synthesizing polysomes selectively isolated from a mouse parietal yolk sac carcinoma (PYS-2) were used for translation in an heterologous cell-free system. Translation products were collagenase-sensitive and displayed an electrophoretic mobility correspondent to type IV collagen. Translation released mRNA was employed to construct a 100 base pairs long cDNA clone which hybridized to a 7,800 nucleotides long mRNA. Peptides synthesized by "in vitro" translation of hybrid selected mRNA displayed an electrophoretic mobility compatible with that of alpha 1 (IV) collagen, were sensitive to collagenase and were immunoprecipitated by anti-type IV collagen antibody.